hNaf1 is required for accumulation of human box H/ACA snoRNPs, scaRNPs, and telomerase - Hoareau-Aveilla, Coralie (Cold Spring Harbor Laboratory Press, 2006)
The human telomerase ribonucleoprotein particle (RNP) shares with box H/ACA small Cajal body (sca)RNPs and small nucleolar (sno)RNPs the proteins dyskerin, hGar1, hNhp2, and hNop10. How dyskerin, hGar1, hNhp2, and hNop10 assemble with box H/ACA scaRNAs, snoRNAs, and the RNA component of telomerase (hTR) in vivo remains unknown. In yeast, Naf1p interacts with H/ACA snoRNP proteins and may promote assembly of Cbf5p (the yeast ortholog of dyskerin) with nascent pre-snoRNAs. Here we show that the human HsQ96HR8 protein, thereafter termed hNaf1, can functionally replace endogenous Naf1p in yeast. HeLa hNaf1 associates with dyskerin and hNop10 as well as box H/ACA scaRNAs, snoRNAs, and hTR. Reduction of hNaf1 steady-state levels by RNAi significantly lowers accumulation of these components of box H/ACA scaRNP, snoRNP, and telomerase. hNaf1 is found predominantly in numerous discrete foci in the nucleoplasm and fails to accumulate within Cajal bodies or nucleoli. Altogether, these results suggest that hNaf1 intervenes in early assembly steps of human box H/ACA RNPs, including telomerase.